PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA BADAN PENDAPATAN DAERAH (BAPENDA) KOTA PADANG - Jhon Fernos; Istitkharah Wipi (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2023)
This study aims to determine the effect of compensation and motivation on employee performance at the Regional Revenue Agency (Bapenda) Padang City. This type of research is quantitative research. The sample consisted of 75 employees of the Regional Revenue Agency (Bapenda) Padang City using total sampling. Data analysis used is multiple linear regression analysis, classical assumption test, and hypothesis testing. The results showed that the Compensation and Motivation variables partially had a positive and significant effect on the performance of employees at the Regional Revenue Agency (Bappenda) Padang City